Risk Factors for Enterocolitis after the Definitive Treatment of Hirschsprung’s Disease - Choudhury, Kamal M; Hoque, Shafiqul (TAJ: Journal of Teachers Association, 2011)
DOI: http://dx.doi.org/10.3329/taj.v15i1.8374 TAJ 2002; 15(1): 13-16